Breaking the silence: Barriers to help-seeking among female victims of domestic violence in Ardabil, Iran - A qualitative study. - Samaneh Dabagh Fekri; Negar Khoshnevis; Armin Zareiyan; Elham Kheirkhahi; Zahra Behboodi Moghadam; Masoumeh Namazi (PLoS ONE)
Background Globally, 1 in 3 women (approximately 30%) experience physical or sexual violence in their lifetime, with intimate partner violence being the most common form Therefore, official support for women victims of domestic violence, as the most important individuals in achieving sustainable development goals, leads to improved health and empowerment of women, ultimately increasing their productivity in society. The present study aimed to elucidate understanding and experiences of Iranian victims of domestic violence regarding barriers to seeking help. Methods The present qualitative study employed purposive sampling and in-depth semi-structured interviews with 20 women who were victims of domestic violence from July 2023 to March 2024 at the Legal Medicine Organization, Ardabil, Iran. Qualitative content analysis was conducted conventionally using the method proposed by Zhang and Wildemuth (2016) with MAXQDA software version 10, VERBI Software GmbH, Berlin. Results The age range of the participants was 15-45 years old with an average age of 30.65 years and the educational level of them ranged from elementary school to postgraduate degrees. The educational backgrounds of their spouses varied from elementary school to doctorate degree. The data analysis yielded three main categories and twelve Subcategories. The categories included "structural and economic barriers to empowerment", "ineffective support providers", "and efforts and struggles to preserve the family". Conclusion This study findings underscore a challenging reality for women, indicating a lengthy journey to assert their rights. Societal support for victims of domestic violence is insufficient, which exacerbates the situation, leading to further exploitation by men and heightened levels of violence. Victims of domestic violence require immediate access to specialized services, financial and moral support from official agencies and facilitating the formal help-seeking process.